The Legal Profession as an Object of Study - Zolezzi Ibarcena, Lorenzo (1970)
This paper analyzes the lawyer's profession through a sociological approach and different researches that have been carried out on the subject. In this way, the author addresses issues related to the description, organization and division of the profession, morale, the professional income of lawyers, the economic power of clients, the position within the profession, among other aspects. However, the article concludes by pointing out that lawyers have a role of social control, through which they can redirect, or not, the expectations of clients and the social interest in accordance with the law.